Dried peel fraction of Citrus sinensis partially reverses pathological changes in rat model of liver cirrhosis - Ali, Shakir; Prasad, Ram; Naime, Mohammed; Zafar, Hina; Mahmood, Amena; Routray, Indusmita; Şahin, Kazım (Ios Press, 2011)
Citrus sinensis is a seasonal fruit. Its zester is rich in bioactive phytochemicals, such as limonene, b-sitosterol, and ascorbic acid, which possess pharmacological action. In this study, we report the effect of fraction prepared from dried peel of C. sinensis on biochemical and histopathological changes in rat model of liver cirrhosis. Liver cirrhosis was induced in rats by administering thioacetamide at a concentration of 0.03% in drinking water for 16 weeks. Thioacetamide was discontinued after 16 weeks and from the 18th week rats were given the extract orally for 9 weeks. Following the completion of the treatment, animals were killed and biochemical and histopathological changes associated with liver cirrhosis were evaluated. The treatment was found to reverse the elevated levels of alkaline phosphatase, c-glutamyl transferase, and other biochemical markers related to oxidative stress and selected drug metabolizing enzymes. Histopathology of the hepatic tissue confirmed the curative effect of the extract, and corroborated with the biochemical findings. HPTLC fingerprinting of the test fraction confirmed the presence of limonene, b-sitosterol, and ascorbic acid, which may partially explain the effect. The extract was also found to possess the anti-proliferative activity, determined by measuring the incorporation of radioactive thymidine by the hepatic DNA. The study indicates the inhibitory action of the test preparation on collagen accumulation in the extracellular matrix, and hence suggests its use as a potential therapeutic agent in liver fibrosis and cirrhosis.
Keywords: Citrus sinensis; Liver cirrhosis; Animal model